Physicochemical Nutritional and Sensory Properties of Kluklui Supplemented With Porang Glucomannan and Banana Flour - Eni Harmayani; Nasser Farid Geraldo; Agnes Murdiati (Indonesian Food and Nutrition Progress, 2021)
The meal from peanut oil-extraction may be valorized as snacks for human food. In Benin, West Africa, this peanut meal is traditionally used to produce snack food called kluiklui. The snacks were obtained by frying partially defatted peanut paste rolled into sticks. In order to improve sensory, physicochemical and nutritional content of kluiklui, different types of flour enriched kluiklui (FEK) were produced by incorporating native banana flour, or type-3 resistant starch banana flour at two levels (4 and 5%) and 1% porang glucomannan (mass basis) in this study. The produced kluiklui were evaluated for physicochemical, sensory and nutritional properties and were compared with a control kluiklui made from 100% partially defatted peanut paste. The samples with 1% porang glucomannan and those with combination of 4% type-3 resistant starch banana flour and 1% porang glucomannan achieved the highest consumer acceptance with overall acceptability value 5.53 and 5.40, respectively. The developed products were found to be highly nutritious in terms of protein and carbohydrate. However, the products had higher value of moisture content and required further drying. The indigestible fraction was also increased in the formulated kluiklui which is attributed to the synergistic presence of fiber. Sample containing 4% type-3 resistant starch banana flour and 1% porang glucomannan exhibited the highest indigestible fraction content (30.76%). Our results showed that the nutritionally and sensory accepted flour enriched kluiklui can be prepared using banana flour and porang glucomannan.